Estudos acerca de duas formulações da cosmologia Newtoniana: discreta e contínua - Nascimento, Francinaldo Florencio do (2016)
We considered the discrete approach to Newtonian cosmology presented by Ellis and Gibbons in a recent paper, and generalize this to the continuum limit. The results are obtained using the Newton's laws for particles interacting gravitationally, which are moving homothetically, with with their comoving positions constituting a central configuration. It requines no use of the fluid mechanics, but just a correspondence between the quantities which appear in the approach of Ellis and Gibbons and their generalizations for a system with high density, but with a finite number of particles. The solutions of the equation for the scale factor are presented, taking into account the presence of a term associated with the cosmological constant. We briefly present the relativistic cosmology and compare with Newtonian cosmology.